EFEKTIFITAS MODIFIKASI MODERN DRESSING DAN TERAPI OZON TERHADAP PENYEMBUHAN LUKA PADA PASIEN DENGAN PRESSURE ULCER DI WOCARE CLINIC BOGOR - NURMALYA MEGAWATI, VNNY; HAKIMI, H. MUHAMMAD (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2015)
Pressure ulcers have some treatment steps, consisting of : 1) wound management, 2) surgical management, and 3) therapeutic devices. One of the complementary therapies is ozone therapy. Ozone therapy has anti-bacterial, anti-viral, anti-fungal and anti-protozoal agents to heal the wound. The purpose of this study is to identify the effectiveness of modern dressing modification and ozone therapy for wound healing in patients with pressure ulcers.This study used a quasi-experimental design, with non-equivalent control group design. The population was all patients who had pressure ulcers Wocare Clinic in Bogor, and the number of samples was 16, divided into experimental group and control group, chosen by consecutive sampling technique. Instruments used were Bates Jansen Wound Assessment Tools for identifying accelerated wound healing. After the data were collected, they were processed and analyzed using univariate and bivariate with paired t-Test and independent t?Test. The results of the statistical test using Independent t-Test demonstrated the value of ? = 0,000 < 0,05. Therefore, it can be concluded that “The use of modern modification of dressings and ozone therapy more effective on wound healing compared with the use of modern dressings course in patients with pressure ulcers". These results are consistent with the theories that support this study. Hence, it is suggested that future research on this topic are control the confounding factors and increase the number of respondents.Keywords : pressure ulcer, modern dressing, ozone therapy, wound healing